Potential Role of African Fermented Indigenous Vegetables in Maternal and Child Nutrition in Sub-Saharan Africa - Marie Lys Irakoze; Eliud N. Wafula; Eddy Owaga (International Journal of Food Science)
Hunger and malnutrition continue to affect Africa especially the vulnerable children and women in reproductive age. However, Africa has indigenous foods and associated traditional technologies that can contribute to alleviation of hunger, malnutrition, and communicable and noncommunicable diseases. The importance of African indigenous vegetables is undeniable, only that they are season-linked and considered as “food for poor” despite their high nutritional contents. The utilization of African indigenous vegetables (AIVs) is hindered by postharvest losses and antinutrients affecting the bioavailability of nutrients. In Africa, fermentation is among the oldest food processing technologies with long history of safe use. Apart from extending shelf life and improving food organoleptic properties, fermentation of African indigenous vegetables (AIVs) is known to improve food nutritional values such as proteins, minerals, vitamins, and other beneficial phytochemicals. It can also increase bioavailability of various vitamins, minerals, and phytochemicals and increase synthesis of vital blood pressure regulators thus protecting against cardiovascular diseases and cancer and further helping fight certain malnutrition deficiencies. Some lactic acid bacteria (LAB) involved in food fermentation are known to produce exopolysaccharides with cholesterol-lowering, immunomodulator, antioxidant, and anticancer properties. Fermented foods (vegetables) are superior in quality and safety since most microorganisms involved in fermentation are good starter cultures that can inhibit the growth of foodborne pathogens and detoxify harmful compounds in foods. Thus, fermented foods can boost growth and well-being in children and women due to their higher nutritional contents. Therefore, fermentation of AIVs can contribute to the attainment of food and nutrition security especially among women and children who rely on these vegetables as a staple source of micronutrients and income. These benefits have a positive impact on the implementation of the second sustainable development goals and African Union agenda 2063. This review is aimed at shedding light on the potential of African fermented indigenous vegetables in combating maternal and child malnutrition in Sub-Sahara Africa.